Análise espacial de coinfecção TB/HIV em microrregiões do Brasil de 2007 a 2011 - Loriato, Karina Covre (2017)
Introduction: Human immunodeficiency virus (HIV) infection is an important risk factor for tuberculosis (TB). Knowledge of the spatial distribution and dependence of tuberculosis and HIV/AIDS cases in Brazil will allow the visualization of its geographical distribution and the frequency of occurrence of coinfection in space/time. Objectives: To characterize the demographic and clinical aspects of the cases of TB/HIV/AIDS coinfection and to analyze the spatial dependence of epidemiological data on these cases in the micro-regions of Brazil with the use of geoprocessing tools. Methods: The study comprises 558 micro regions of the Brazilian territory. It is an ecological study in which the SINAN tuberculosis notification database was used. Demographic and clinical epidemiological profile was performed. For the spatial analysis, the Moran index, local empirical bayesian estimator (LEbayes), the global empirical Bayesian estimator (GEbayes) and the Poisson model were used. Results: The final sample of the study was 33,773 notifications of new cases of tuberculosis in HIV/AIDS patients. In the profile, 23,621 individuals (69.94%) were male; 15,882 (54.46%) were declared black or brown; 19,216 (56.9%) were aged 15 to 39 years; and 10,484 (41.09%) had between one and three years of study. Regarding clinical aspects, 24,654 (84.71%) had suspected X-ray of TB and sputum smear microscopy was positive in 12,194 (51.11%) collected samples. The most common form of tuberculosis was pulmonary tuberculosis, in 21,100 (62.5%). Cure was reported in 17,288 (53.93%) cases, abandonment occurred in 4,575 cases (14.27%) and 5,340 (16.65%) died. The Moran index showed a weak and significant spatial correlation, being the index value 0.265481 and p-value of 0.01. Conclusions: The results showed that TB/HIV/AIDS coinfection occurs mainly in men aged 15-39, browns and blacks with up to six years of study, and does present an weak overall pattern of dependence in space.